Exploring the potential of Scabiosa columbaria in Alzheimer's disease treatment: An in silico approach - Riyan A.P. Irsal, M.Si; Gusnia M. Gholam, M.Si; Maheswari A. Dwicesaria, M.Si; Tiyara F. Mansyah, S.Si; Fernanda Chairunisa, M.Si (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: يعد مرض الزهايمر تهديدا عالميا متزايدا، ولا يوجد علاج فعال له حاليا. ولذلك، تهدف هذه الدراسة إلى استكشاف المركبات النباتية في نبات الجرباء العمودية كمثبطات لإنزيم أسيتيل كولين إستيراز، وإنزيم شطر البروتين السلائف للأميلويد بيتا 1، وإنزيم محول عامل نخر الورم ألفا في مرض الزهايمر. يحتوي نبات الجرباء العمودية عادة على مركبات نشطة بيولوجيا مختلفة، مثل حمض الكلوروجينيك، واللينالول، والكاتيكين، المعروفة بخصائصها في إزالة السموم، والقدرة على التغلب على احتباس الرطوبة السامة، والآليات العلاجية في كوفيد-19. وقد أظهرت العديد من الدراسات أيضا أن المستخلص له نشاط مضاد للأكسدة قوي، مما قد يقلل من الالتهاب العصبي في مرض الزهايمر. في هذا السياق، توفر هذه الدراسة الحالية فرصا لتطوير المواد الكيميائية النباتية لنبات الجرباء العمودية كمرشحين علاجيين جدد لمرض الزهايمر من خلال دراسة التفاعلات مع الإنزيمات الرئيسية. طرق البحث: تم تقييم 27 مركبا نباتيا للنشاط التثبيطي ضد الإنزيمات المستهدفة باستخدام برنامج ''ياسارا ستركتشر''. تم تقييم الخصائص الدوائية والحركية والأيضية والسمية للمركبات. خضعت المركبات الأعلى تصنيفا لمحاكاة ديناميكية جزيئية لمدة 100 نانوثانية. النتائج: استوفت جميع المركبات معايير ''ليبينسكي'' مع انخفاض كبير في السمية. أظهرت الكاتيكينات نشاطا تثبيطيا أكبر وتفاعلات إضافية مع إنزيم أسيتيل كولين إستيراز مقارنة بدواء الجالانتامين. أظهر حمض الكلوروجينيك نشاطا تثبيطيا أقوى ضد إنزيم محول عامل نخر الورم ألفا مقارنة بدواء المراقبة. أظهرت المحاكاة الديناميكية الجزيئية استقرارا جيدا للمعقدات المتكونة، ولكنها تتطلب المزيد من الاستكشاف. الاستنتاجات: أظهرت المركبات المشتقة من نبات الجرباء العمودية إمكانات واعدة كمرشحات دوائية لمرض الزهايمر، خاصة حمض الكلوروجينيك في تفاعله مع إنزيم محول عامل نخر الورم ألفا. أكدت المحاكاة الديناميكية الجزيئية وحسابات الطاقة استقرار وقوة الروابط بين المركبات والبروتينات المستهدفة، مما يشير إلى إمكانية تطوير هذه المركبات كعلاجات محتملة لمرض الزهايمر. Abstract: Objectives: Alzheimer's disease (AD) is posing an increasing global threat and currently lacks effective treatments. Therefore, this study was aimed at exploring phytochemicals in Scabiosa columbaria (S. columbaria) as inhibitors of acetylcholinesterase (AChE), β-site APP cleavage enzyme 1 (BACE1), and TNF-α converting enzyme (TACE) in AD. S. columbaria contains various bioactive compounds, such as chlorogenic acid, linalool, and catechins, which are known for their detoxification properties, capacity to resist and manage harmful moisture buildup, and therapeutic roles in COVID-19. Several studies have also shown that S. columbaria extract has strong antioxidant activity, and may potentially decrease neuroinflammation in AD. Therefore, this study investigated the interactions between S. columbaria phytochemicals and key enzymes associated with AD, thus providing opportunities for the development of new therapeutic candidates. Methods: A total of 27 phytochemicals were evaluated for their inhibitory activity against AChE, BACE1, and TACE with YASARA Structure. ADMET profiles and toxicity were assessed. The top candidate compounds underwent 100 ns MD simulations. Results: All ligands met Lipinski's rule and showed low toxicity. Catechins, compared with the known drug galantamine, showed higher inhibitory activity and interacted with additional active sites on AChE, thus suggesting potentially higher efficacy. Moreover, chlorogenic acid showed stronger inhibitory activity against TACE than the control drug (aryl-sulfonamide), thereby suggesting a different mechanism of action. MD simulation revealed that the formed complexes had good stability. However, further exploration is necessary. Conclusion: S. columbaria derivative compounds are promising drug candidates because of their properties, including the affinity of chlorogenic acid toward TACE and hydrogen bond enhancing ligand–receptor interactions. MD simulation indicated stable ligand–protein complexes, and the radius of gyration and MM-PBSA calculations revealed favorable binding and interaction energies. Our findings demonstrate the identified compounds' potential for further drug development.